Analysis of the effect of global climate change on ground source heat pump systems in different climate categories. (June 2015) - Kharseh, Mohamad; Altorkmany, Lobna; Al-Khawaja, Mohammed; Hassani, Ferri
Abstract: Ground source heat pump (GSHP) systems exhibit high thermal performance. Consequently, they are increasingly used to heat and cool buildings. The thermal performance of GSHP systems strongly depends on the operation ground temperature and thermal quality of the building envelope (TQBE). The operation ground temperature is a function of mean annual air temperature and annual thermal load of the building. The thermal load depends on the TQBE and outside temperature. Given that ongoing global climate change (GCC) affects air temperatures, it also affects the performance of GSHP systems. The magnitude of this impact on a given GSHP system strongly depends on local weather conditions and the TQBE. The overall aim of the current study is to investigate the impact of GCC on the performance of GSHP systems in different climate. To achieve this aim, three cities located in three climate categories were considered: Stockholm, Sweden (cold), Istanbul, Turkey (mild), and Doha, Qatar (hot). In each city, two buildings were modeled. One was built according to current local building regulations, while the other was built to have a TQBE lower than the standard TQBE. Simulations were run for present (2014) and future (projected for 2050) outdoor designing conditions. Highlights: Heating/cooling loads have different sensitivity to warming in different climates. In different climate, warming has different impact on the energy of GSHP systems. Improving TQBE reduces heating load, while it might increase cooling load. Improving TQBE reduces the impact of GW on driving energy of GSHP systems. Driving energy of GSHP has different sensitivity to TQBE in different climates.